Students’ perspectives on cause-related marketing: The case study of the book publishing industry - Pashootanizadeh, Mitra; Amini, Maryam (Malaysian Journal of Library and Information Science, 2022)
The book publishing industry and its market in Iran are not very prosperous for various reasons, and activists in this situation need to apply some cause-related marketing (CRM) strategies to attract customers. For this reason, this study was conducted to determine the perspectives of university students on CRM in the book publishing industry. The survey research design was used to achieve the objective of the study. Literature and humanities university students from University of Tehran, Iran, were identified as the target group to gauge their perspectives on CRM by book publishers. This is due to the importance of books in humanities and studying literature. A total of 261 (81.5% response rate) students completed the survey questionnaire. The findings demonstrate that CRM by book publishers and bookstores influences on students purchasing decisions. In this regard, it was vital for students as customers to know where the book publishers or booksellers spent their money on. Findings on various charity’s affairs practices on spending book purchase money showed that the top priority are related to books, education, and children. Since students tend to purchase textbooks, it is suggested that textbook publishers take the lead in CRM through mass media, online advertising, social web and messaging platforms to help introduce and institutionalize this marketing strategy. As this is the first study in Iran that reports students’ perspectives in applying CRM strategies to attract customers in buying books, it has paved the way for further research. It would be useful to make more informed decisions about CRM strategies in the Iranian publishing and book industry and creating a positive effect on book purchase intention.